The psychological experience of resource-based learning (RBL) within the South African higher education context - Somarie Holtzhausen; Laetus Lategan (Acta Academica)
South African higher education is currencly characterised by massification, globalisation, an increase in non-traditional students entering the system and a paradigm shift from lecture-based to resource-based education (RBL). During the transformation of the South African higher education system, RBL was proposed by theneducation ministry and in various policy documents as a mode of delivery which could meet che challenges of learners' expectations, the realities of che work place, and the need co maintain a high standard of graduates. Such an experience of change is difficult, due co its complexity and pace. In chis article accencion is focused on facilitators' and co-ordinators' psychological experiences of higher educational change in an RBL programme.